Development of a System for Computer-assisted Learning of Croatian Orthography Concerning the Yat Reflex (CAL-COR) - Grmača, Dolores; Kubelka, Ozren; Ljubešić, Nikola (2005)
This paper describes the development of the system for computer-assisted learning of Croatian orthography concerning the yat reflex (CAL-COR). Our previous research resulted in an online example-based system (http://calcor.ffzg.hr) with already two versions that are described in this paper. The improvement of the system includes changes in the algorithm that takes control of the learning process in a greater fashion. Further improvement is made in the construction of the user's profile which will enable further research and a more specific approach to the learning process concerning user's age, foreknowledge and learning abilities. Also, a visibility plan is developed aiming to popularize such system in educational institutions and broader. Frequent usage of the system is of great importance for collecting data which will enable further optimization of the system.
Projekt MZOS
ENG